Efeito residual do herbicida Flumioxazina, no desenvolvimento e produtividade do trigo (Triticum aestivum) - Santos, Elyoenay Gadyel dos (2021)
Wheat (Triticum aestivum) has an important role in the world market, as well as being the raw material for various food products, both animal and human. In Brazil, its production stands out with 5,531.8 thousand tons of cereal (CONAB, 2019). Due to this importance, the care in crop management should be prioritized, including care with the chemical shortage period, used before during and after the implantation of the crop. In this sense, the present work aimed to evaluate possible residual effects harmful to wheat, caused by applications at times not recommended by the herbicide flumioxazin, in the desiccation of the bean (Phaseolus vulgaris). The experiment was carried out with a randomized block design, containing four replications. The treatments were carried out based on the desiccation applications with flumioxazin herbicide in the dosage of 0.6 g for 5 liters of syrup. The treatments were composed by the application of the herbicide at 40, 30, 20, 10, and 0 days before sowing the wheat, with or without the addition of adjuvant. The evaluations of phytotoxicity, plant structure, and yield components were performed at 15 and 30 DAE (days after emergence). When analyzing and interpreting the data, significant interference can be observed for the variables plant height, a number of leaves, tiller, green mass, dry mass, in applications of 10 to 20 days without the use of an adjuvant, compared to the control, both for evaluation 15 to 30 days after the emergence of the culture. As for the yield component variables, only ear size and number of spikelets showed a reduction with the use of flumioxazin without adjuvant at 20 and 30 DAS compared to the control, the other variables number of grains, the mass of a thousand grains, and stand did not suffer any. interference compares the witness.